Pengaruh Pembiasaan Asmaul Husna di Sekolah terhadap Akhlak Bullying Peserta Didik SDN 04 Gambuhan - Khafidotun Nafsiyah; Asmaji Mochtar; Toha Makhsun (Mathematics Education Study Program, 2025)
This study aimed to investigate the impact of regular Asmaul Husna practice in schools on bullying behavior among students of SDN 04 Gambuhan. Employing a descriptive qualitative approach, this research sought to describe real-world phenomena as they occurred. Data was collected through observation, interviews, and document analysis. The findings indicated a significant positive correlation between the practice of Asmaul Husna and a reduction in bullying behavior. As students engaged more frequently in reciting Asmaul Husna as a form of remembrance (dhikr) and supplication, they exhibited decreased bullying tendencies toward their peers. Moreover, collaborative Asmaul Husna practice fostered a sense of appreciation, happiness, camaraderie, love, and respect among students, contributing to the development of positive character traits and good conduct in their daily lives. Additionally, a significant positive correlation was found between students' attitudes towards Asmaul Husna practice and their academic achievement.